KUALITAS PELAYANAN KREDIT USAHA RAKYAT DI BRI UNIT GIANYAR - Puspita Dewi, Desak Putu Rany; Yudartha, I Putu Dharmanu; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2019)
ABSTRACT One of the missions of Bank Rakyat Unit Gianyar is Providing excellent service to customers through a wide-spread network and supported by professional human resources and reliable information technology by implementing risk management and excellent Good Corporate Governance (GCG) practices, however, this goal is not yet in line with the requirements. Therefore, the writer wants to find out the quality of service by using qualitative methods and using the quality of service as a reference, then using interactive analysis techniques Miles and Huberman to provide conclusions and verification. The result of this research shows that the quality of BRI Unit Gianyar’s KUR services already occupiedd service qualityy dimensions. Keywords: Public Services, Quality Services, KUR Services